THE CONCEPT OF TAWAZUN IN ENVIRONMENTAL MANAGEMENT: INTEGRATION OF SOCIAL, ECONOMIC, AND ECOLOGICAL BALANCE - Mega Oktaviany; Marningot Tua Natalis Situmorang; Rahimah Embong; Mitra Sami Gultom; Mujakir; Muhammad Alif (Universitas Muhammadiyah Prof DR HAMKA, 2026)
Research aims: This article examines the application of the concept of Tawazun in environmental management in Indonesia, focusing on the balance between social, economic, and ecological aspects to achieve sustainability. Design/Methodology/Approach: This research employs a qualitative approach, utilizing case studies to analyze policies and practices implemented, such as the Climate Village Program (Proklim) and Nirwasita Tantra, which reflect efforts to integrate the three aspects of natural resource management. Research findings: The results indicate that applying the Tawazun principle can enhance the effectiveness of environmental management by fostering cross-sectoral synergies among the government, the private sector, and the community. For example, the Proklim program, which focuses on community empowerment to mitigate the impact of climate change, has successfully integrated social, economic, and environmental conservation dimensions. Current data (as of 2024) shows Proklim covers over 6,500 locations across Indonesia, with 391 achieving the highest 'Lestari' category, reflecting sustained community-based mitigation and adaptation efforts. Similarly, the Nirwasita Tantra policy, which provides incentives for regions with the best environmental performance, also considers social and economic impacts. In 2023, this award was given to 11 Best Regional Leaders (Governors, Mayors, and Regents), demonstrating the policy's success in promoting integrated and balanced regional environmental governance. Theoretical Contribution/Originality: The concept of Tawazun, meaning balance or harmony, emphasizes the importance of integrating these three dimensions into any environmental management policy. Practitioners/Policy Implications: This research suggests the adoption of an inclusive and evidence-based approach to policy, involving all stakeholders from the planning to evaluation stages. Research Limitations/Implications: Significant challenges persist in implementing the Tawazun principle, including inadequate coordination between sectors, limited resources, and low community engagement. Sectoral coordination issues and socio-economic imbalances frequently hinder the attainment of an optimal balance.